Trends in nutritional status and nutrient intakes and correlates of overweight/obesity among rural adult women (≥18–60 years) in India: National Nutrition Monitoring Bureau (NNMB) national surveys. Issue 5 (7th August 2015) - Meshram, II; Balakrishna, N; Sreeramakrishna, K; Rao, K Mallikharjun; Kumar, R Hari; Arlappa, N; Manohar, G; Reddy, Ch Gal; Ravindranath, M; Kumar, S Sharad; Brahmam, GNV; Laxmaiah, A
Abstract: Objective: To assess trends in nutrient intakes and nutritional status of rural adult women (≥18–60 years) and the association of sociodemographic characteristics with overweight/obesity. Design: Community-based cross-sectional studies carried out during 1975–79 to 2011–12 by the National Nutrition Monitoring Bureau (NNMB) were used. Anthropometric measurements such as height, weight and waist circumference, carried out during the surveys, were used. Association and logistic regression analyses between sociodemographic characteristics and overweight/obesity and abdominal obesity were conducted using a complex samples procedure. Setting: Ten NNMB states of India. Subjects: Non-pregnant and non-lactating rural women aged ≥18–60 years covered during the above periods from ten states in India. Results: The prevalence of chronic energy deficiency has declined from 52 % during 1975–79 to 34 % during 2011–12, while that of overweight/obesity has increased from 7 % to 24 % during the same period. Median intakes of most of the nutrients have increased over the same period, although they were below recommended levels. The chance of overweight/obesity and abdominal obesity was significantly ( P <0·01) higher among women aged 40–60 years, those belonging to Christian religion and other backward communities, women living in pucca houses, literate women, women engaged in service and business, and those having higher per capita income. Conclusions: Prevalence of chronic energy deficiency has declined significantly; however, overweight/obesity has increased during the same period. This increase in overweight/obesity may be attributed to increased consumption of fatty foods, sedentary lifestyle and improved socio-economic status. There is a need to educate the community about regular physical exercise, low intakes of fats and oils, and a balanced diet.